2018
DOI: 10.6118/jmm.2018.24.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Acute Postoperative Urinary Retention after Transvaginal Uterosacral Suspension Surgery

Abstract: ObjectivesTo investigate the rate of postoperative urinary retention (POUR) and identify the risk factors for this complication in women who underwent transvaginal uterosacral suspension surgery.MethodsA retrospective chart review was conducted for 75 women who underwent transvaginal uterosacral suspension surgery with vaginal hysterectomy, repair of cystocele, and levator myorrhaphy with/without transobturator anti-incontinence surgery. POUR was defined as a need for continuous intermittent catheterization on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
5
0
6
Order By: Relevance
“…While elevated preoperative PVR tends to resolve after pelvic organ prolapse surgery in the long term, 14 its impact on immediate POUR has been controversial. Two studies demonstrating that elevated preoperative PVR was associated with acute POUR were limited to uterosacral suspensions 15 and transobturator tape procedures 16 . Another study only included women who underwent pelvic floor repair without concurrent incontinence procedures 17 while one recent study excluded patients with preoperative PVR more than 150 ml 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While elevated preoperative PVR tends to resolve after pelvic organ prolapse surgery in the long term, 14 its impact on immediate POUR has been controversial. Two studies demonstrating that elevated preoperative PVR was associated with acute POUR were limited to uterosacral suspensions 15 and transobturator tape procedures 16 . Another study only included women who underwent pelvic floor repair without concurrent incontinence procedures 17 while one recent study excluded patients with preoperative PVR more than 150 ml 18 .…”
Section: Discussionmentioning
confidence: 99%
“…13 While elevated preoperative PVR tends to resolve after pelvic organ prolapse surgery in the long term, 14 its impact on immediate POUR has been controversial. Two studies demonstrating that elevated preoperative PVR was associated with acute POUR were limited to uterosacral suspensions 15 and transobturator tape procedures. 16 Another study Note: In particular, score of 2 (n = 6) and 3 (n = 62) were combined, as well as, for score of 9 (n = 13), 10 (n = 8) and 11 (n = 5).…”
Section: Discussionmentioning
confidence: 99%
“…High PVRs can be caused by bladder outlet obstruction (BOO) or bladder underactivity [26] . Son EJ et al [27] discovered a connection between PVR and POUR and suggested that PVR over 30% of total bladder capacity should be considered a predictor of POUR following vaginal reconstructive surgery. Lo TS et al [22] proposed that PVR greater than 200ml is an independent risk factor of the development of POUR.…”
Section: Discussionmentioning
confidence: 99%
“…Higher PVR generally indicates increased outlet resistance, decreased bladder contractility and storage disorders or disorders of emptying [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Porous synthetic tapes (sling) have been globally used in such surgeries [8]; although this procedure has a high cure rate for SUI after 12 months, severe complications as erosion has been associated with the poor biocompatibility and inadequate biomechanical properties of polypropylene mesh-as lack of elasticity and high stiffness-when it is implanted into the pelvic floor [9,10]. Urinary retention has been a common postoperative complication [11,12]. If urinary retention persists, it can damage surgical repair and cause urinary tract infection.…”
Section: Introductionmentioning
confidence: 99%